Quantitative Analysis of Interfacial Area on Liquid-liquid Multiphase Flow of Transesterification Process in Cross-junction Microchannel Reactor - Kuzilati Kushaari; Afiq Mohd Laziz; Nor Hisham Hamid (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
Key advantage of microfluidic technology in chemical processing is the high interfacial area which is especially important factors in multiphase reaction. The multiphase reaction like transesterification of vegetable oil and methanol to produce biodiesel are largely dependent on interfacial area for better mass transfer. However, little attentions have been given to the hydrodynamic factor which affects the interfacial area in a microchannel. In this study, the interfacial area from the droplet flow regime was studied by varying the parameter of methanol to oil ratio (M/O), total flow rate (QTotal) and catalyst concentration. The droplet flow was created by a cross-junction channel and photos were made to measure the size of the droplets with help of microscope. The maximum M/O ratio of 23 and lowest flow rate of 10 Î¼L/min exhibited the highest interfacial area, where increasing M/O by 67% could increase the interfacial area by 23%. By varying the KOH catalyst concentration, the change in the interfacial area was very small, hence showing the lowest impact on the interfacial area of the droplet. Therefore, further analysis must be performed to investigate the impact of interfacial area and mass transfer coefficient on the reaction performance to produce highest yield of biodiesel in microchannel reactor.